2005
DOI: 10.4310/cms.2005.v3.n2.a7
|View full text |Cite
|
Sign up to set email alerts
|

Axial Symmetry and Classification of Stationary Solutions of Doi-Onsager Equation on the Sphere with Maier-Saupe Potential

Abstract: This note serves to provide additional details for the proof of Lemma 3.6 in our paper [Liu, Zhang and Zhang, Comm. Math. Sci., 3(2005), pp.201-218]. Moreover, we will also present an alternative, yet simpler, proof based on arguments in [Wang, Zhang and Zhang, CPAM, 68(2015), no. 8, 1326-1398.In [1] we showed that in order to determine the number of solutions to the Doi-Onsager equation on the sphere with Maier-Saupe potential, it suffices to determine the number of zeros of B(η, α) in term of the intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
123
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(128 citation statements)
references
References 16 publications
4
123
1
Order By: Relevance
“…In this case, equation (79) with equilibrium probability density given in (78) reduces to the case of pure (non-dipolar) nematic polymers. From the theoretical results of pure nematic polymers [11,15,19], we know that for b > 7.5 there is only one family of rotation-equivalent prolate equilibrium states. In the analysis below we fix b = 8.…”
mentioning
confidence: 99%
“…In this case, equation (79) with equilibrium probability density given in (78) reduces to the case of pure (non-dipolar) nematic polymers. From the theoretical results of pure nematic polymers [11,15,19], we know that for b > 7.5 there is only one family of rotation-equivalent prolate equilibrium states. In the analysis below we fix b = 8.…”
mentioning
confidence: 99%
“…It has been shown that in the absence of external field, all equilibrium states of nematic polymers are axisymmetric [8,24,35]. Without loss of generality, we assume the m 3 -axis is the axis of symmetry.…”
Section: Equilibrium States Of a Nematic Polymer Ensemblementioning
confidence: 99%
“…One mathematical advance in the understanding of the equilibrium states of the Doi model is the rigorous proof on that the equilibria of the Smoluchowski equation with the Maier-Saupe potential are uniaxial [8,24,35]. However, it seems more challenging to obtain a solid proof on the stability of the equilibria.…”
Section: Introductionmentioning
confidence: 99%
“…For dissipative gradient systems, the dynamical behavior is characterized by a global attractor which is formed by the steady-states and their unstable manifolds, and all solutions approach a steady-state as t → ∞. Denoting u = ψ exp(V /2), the Lyapunov functional for the Smoluchowski equation is given by F(t) = S 2 ψ(m,t)logu(m,t) dm, which satisfies the equation This transcendental matrix equation is now well understood (see [5], [6], [8], [13], [18])). The isotropic steady stateψ = 1/4π persists for all potential intensities b > 0.…”
Section: Dissipativity and The Global Attractormentioning
confidence: 99%
“…However, it is widely accepted that the Maier-Saupe potential affords sufficient degrees of freedom to capture the dynamics of the micro-micro interaction. In a recent development, the bifurcation diagram for the Onsager equation (and therefore also Smoluchowski equation) with the Maier-Saupe potential was confirmed rigorously (see [5], [6], [8], [13], [18], [19]). The equation undergoes two bifurcations.…”
Section: Introductionmentioning
confidence: 99%